2022
DOI: 10.1038/s41420-022-01143-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of FBXL7 as a novel player in human cancers

Abstract: F-box and leucine-rich repeat protein 7 (FBXL7), an F-box protein responsible for substrate recognition by the SKP1-Cullin-1-F-box (SCF) ubiquitin ligases, plays an emerging role in the regulation of tumorigenesis and tumor progression. FBXL7 promotes polyubiquitylation and degradation of diverse substrates and is involved in many biological processes, including apoptosis, cell proliferation, cell migration and invasion, tumor metastasis, DNA damage, glucose metabolism, planar cell polarity, and drug resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In addition, F-box and leucine-rich repeat protein 7 (FBXL7), an F-box protein that is accountable for substrate recognition in the SKP1-Cullin-1-F-box (SCF) ubiquitin ligases, assumes a growing function in the control of tumorigenesis and tumor progression. FBXL7 induces polyubiquitylation and breakdown of various substrates and is involved in numerous biological processes, including apoptosis, cell proliferation, cell migration and invasion, tumor metastasis, DNA damage, glucose metabolism, planar cell polarity, and drug resistance [ 55 ]. FBXL7 exhibits aberrant expression in a variety of cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, F-box and leucine-rich repeat protein 7 (FBXL7), an F-box protein that is accountable for substrate recognition in the SKP1-Cullin-1-F-box (SCF) ubiquitin ligases, assumes a growing function in the control of tumorigenesis and tumor progression. FBXL7 induces polyubiquitylation and breakdown of various substrates and is involved in numerous biological processes, including apoptosis, cell proliferation, cell migration and invasion, tumor metastasis, DNA damage, glucose metabolism, planar cell polarity, and drug resistance [ 55 ]. FBXL7 exhibits aberrant expression in a variety of cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who exhibited elevated levels of FBXL7 were found to demonstrate poorer OS across multiple cancer types, including colon adenocarcinoma, rectum adenocarcinoma, stomach cancer, liver cancer, thyroid cancer, lung cancer, and urothelial cancer. However, better survival outcomes were observed in kidney renal clear cell carcinoma, which suggests the oncogenic nature of FBXL7 [ 55 ]. WD repeat and high-mobility group box DNA-binding protein 1 (WDHD1), also recognized as acidic nucleoplasmic DNA-binding protein 1 (AND-1), and human chromosome transmission fidelity factor 4 (CTF4), is a relatively evolutionarily conserved protein with 1129 amino acids and homologs in most eukaryotes [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified that ATG10 was associated with autophagy, immune response, and tumor metastasis in HCC ( Zhang J. et al, 2021 ; Chen et al, 2021 ; Xu et al, 2021 ), which suggested that UPS-related genes might contribute to HCC development through regulating biological process. FBXL7, an F-box protein that binds to substrates via SKP1-Cullin-1-F-box (SCF) E3 ubiquitin ligase, could enhance polyubiquitylation and degradation of substrates in tumor occurrence and aggression ( Wang et al, 2022 ). Additionally, FBXL7 reduces chemotherapy resistance by promoting the ubiquitination and degradation of survivin ( Dong et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the addition of melatonin during IVEC prevented the development of blood pressure (Rexhaj et al, 2015) and glucose intolerance (Jia et al, 2022) observed in mice produced via IVEP. The latter effect was associated with restored hepatic expression of Fbxl7, a gene with important roles in apoptosis, cell proliferation, mitochondrial function, cancer development and protection against glucoseinduced cell injury (Ni et al, 2021;Wang et al, 2022b). The use of reproductive (i.e., from the oviduct and uterus) fluids during IVEC seems to be able to promote DNA methylation changes in in vitro-derived porcine blastocysts similar to in vivo counterparts (Canovas et al, 2017), leading to the production of pigs with physiological profiles partially resembling those of AI controls during postnatal development (París-Oller et al, 2022).…”
Section: Can Altered Phenotypes Induced By Art Be Ameliorated?mentioning
confidence: 99%